2023
DOI: 10.3390/biomedicines11010216
|View full text |Cite
|
Sign up to set email alerts
|

The Regional Burden and Disability-Adjusted Life Years of Knee Osteoarthritis in Kazakhstan 2014–2020

Abstract: A Global Burden of Disease (GBD) study reported that 9.6 million years lived with disability (YLDs) were lost due to hip and knee osteoarthritis (KOA) in 2017. Although the GBD study presents the disease burden at the global level, there is no information on any Central Asian country. This study aims to investigate the epidemiology of knee osteoarthritis in Kazakhstan. The data of 56,895 people with KOA between 2014–2020 was derived from the Unified National Electronic Health System of Kazakhstan and retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The higher the level of economic development, the higher the disease burden of osteoarthritis. Similar results were also reported in previous studies [ 20 , 21 ], and an increasing life expectancy is a non-negligible explanation for this result. In 2019, the number of cases and incidence rate of osteoarthritis in China was 10,681,311 and 750.96/100,000, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…The higher the level of economic development, the higher the disease burden of osteoarthritis. Similar results were also reported in previous studies [ 20 , 21 ], and an increasing life expectancy is a non-negligible explanation for this result. In 2019, the number of cases and incidence rate of osteoarthritis in China was 10,681,311 and 750.96/100,000, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Structural changes in the organism for the joint area can cause physical pain, limb dysfunction, the development of psychiatric disorders, and a variety of chronic diseases, which can seriously affect the patient's quality of life. At the same time, there are other risk factors for osteoarthritis of the knee, such as: overweight or obesity, post-sport injuries of the knee, muscle weakness of the lower limbs, knee osteoarthritis, etc [5][6]. The prevalence of osteoarthritis of the knee in the Chinese population is 8.1%, and there is a significant gender difference: women suffer perhaps a heavier burden of disease than men [7].…”
Section: Overview Of Osteoarthritis Of the Kneementioning
confidence: 99%
“…In summary, in recent years, with the aging of China's population rising year by year, the incidence of osteoarthritis of the knee is also on the rise [5], and there is an urgent need for effective clinical as well as rehabilitation treatment measures [60]. In recent years, the prevalence of osteoarthritis of the knee in young adults has also been on the rise, and the increasing incidence and prevalence will bring a heavy burden to the world health system [62].…”
Section: Summary and Prospectsmentioning
confidence: 99%
“…By analyzing the GBD database, Safiri et al ( 9 ) reported the global, regional and national burden of osteoarthritis. Zhakhina et al ( 10 ) reported the disease burden of KOA in Kazakhstan. Similarly, Hoveidaei et al ( 11 ) reported the disease burden of KOA in the Middle East, and Song et al ( 12 ) reported the disease burden of KOA in China.…”
Section: Introductionmentioning
confidence: 99%